メタボリックシンドロームラットによる血管周囲脂肪組織による動脈緊張調節の加齢に伴う変化 - 丸山ー麓, 加菜; 籠田, 智美; 篠塚, 和正; 懐, 理紗; 森川, 花菜 (日本薬理学会年会要旨集, 2022)
Dysfunction of perivascular adipose tissue (PVAT) is related to increased arterial contractility that can lead to the development of cardiovascular diseases. We previously demonstrated that PVAT continued to increase vasodilation in the female SHRSP.Z-Leprfa/IzmDmcr (SHRSP.ZF) rats at 23 weeks (wks) of age, which is the age at which this effect is impaired in the male rats. We therefore investigated whether the compensatory function of PVAT in females disappears with increasing age.Ring preparations of superior mesenteric artery with and without PVAT were obtained from male and female SHRSP.ZF rats aged 23 and 30 wks. Vasodilation to acetylcholine and vasoconstriction to phenylephrine were determined by organ bath methods.In male rats, the vasodilation of arteries without PVAT at 30 wks was lesser than that at 23 wks; however, the presence of PVAT did not affect the vasodilation at either age. In contrast, there was no significant difference in vasodilation of arteries without PVAT between the female rats of either age, while the presence of PVAT increased vasodilation at 23 wks but not at 30 wks. In both sexes, vasoconstriction to phenylephrine was not affected by age or the presence of PVAT.These results demonstrate that the positive effect of PVAT on vasodilation is impaired with ageing in metabolic syndrome, but this impairment develops earlier in the males compared to the females. Thus, sex-related differences in the dysfunction of PVAT along with arterial changes with ageing may explain the difference in incidence of cardiovascular diseases between the sexes.